PENGARUH KOMPETENSI PEDAGOGIK GURU YANG DIPERSEPSIKAN OLEH SISWA TERHADAP HASIL BELAJAR SENI RUPA DALAM MATA PELAJARAN SENI BUDAYA SISWA KELAS VIII SMPN 31 PADANG - Iis Purnama Sari, Dr. Yahya, M.Pd, Dr. Ramalais Hakim, M.Pd (Serupa The Journal of Art Education, 2014)
This Research aimed to obtain information and describe the influence of teachers' pedagogical competence perceived by students on Seni Rupa learning outcomes in subjects Seni Budaya class VIII SMP 31 Padang. While this type of research is quantitative with method descriptive correlational discusses the influence of pedagogical competence of teachers with student learning outcomes. Instrument used was a questionnaire pedagogical competence of teachers are perceived by students. Sources of data in this study are primary data taken directly from the respondents through questionnaires. To analyze the data using descriptive analysis using SPSS version 16.00.The results showed a significant difference between teachers' pedagogical competence perceived by students on learning outcomes of students SMP 31 Padang with tcount 6.123 ttable and 1.984. Variable amount of influence teachers' pedagogical competence perceived by students to the art of learning outcomes in Arts subjects was 27.3% with a level of sig <α (0.000 <0.05). So, to improve learning outcomes on Seni Rupa in subject Seni Budaya student at SMP 31 Padang, the subject teacher Seni Budaya to further improve the learning and pedagogical competence is believed to provide a positive perception of the material by students of Seni Rupa in subject Seni Budaya so that learning outcomes can be improved.Kata Kunci: Kompetensi, Pedagogik, Seni Budaya